The impact of COVID-19 on university students’ self-regulation : a descriptive analysis - Norsimah Dasan,; Balan Rathakrishnan,; Mohamad Idris Bullare,; Lailawati Madlan @ Endalan,; Norkiah Arsat, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic had a major impact on the lives of the entire population of the world. The effect is also felt by students at the university. To pursue a role as a student without face -to -face guidance, the self-regulation factor is very important. The concept of self -regulation is an individual’s beliefs about his or her ability to plan and control behavior. Students at the university need this factor to ensure that the thought patterns and feelings generated are consistent with their role as students to perform academic tasks and at the same time still be able to control behavior from adversely affecting social and environmental. Self -regulation has become a popular scope of study in identifying psychological problems among students towards outstanding academic achievement and personality. However, previous studies have focused less on its relevance in pandemic situations and because of its gap, it became objective in this study by identifying the level of students’ self -regulation during pandemic. The Adolescent Self -Regulation Inventory was used to collect data from 590 students that were selected through simple random sampling. Descriptive analysis such as frequency, percentage and mean values were used. The results showed that 501 (34.9%) students were at the moderate level and 89 (13.9%) students were at the high level and 1.2% of students recorded in low level. The total mean value and standard deviation of self -regulation is 3.26 and 0.38. The mean values for the 27 items of student self -regulation ranged from 1.69 - 4.21. These findings indicate that the level of self -regulation of university students during pandemic is in moderate level. This indicates that the pandemic period did not cause weaknesses in students' self -regulation. However, it needs to be improved. Modules of self-regulation development and its relationship to other variables can be the focus for future studies.